menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Given f(x) = 3x - 1 and g(x)= -x + 6, find f(-2) + g(5). answer choices are: -6 6 8
asked
Dec 16, 2020
138k
views
1
vote
Given f(x) = 3x - 1 and g(x)= -x + 6, find f(-2) + g(5).
answer choices are:
-6
6
8
Mathematics
high-school
Ben Kulbertis
asked
by
Ben Kulbertis
5.2k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
6
votes
Answer:
-6
Explanation:
f(x)=3x-1 g(x)=-x+6
f(-2)=3*(-2)-1 g(5)=-5+6
f(-2)=-7 g(5)=1
f(-2)+g(5)=-7+1=-6
Gracy
answered
Dec 22, 2020
by
Gracy
5.0k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.8m
questions
7.6m
answers
Other Questions
Aliyah has $24 to spend on seven pencils. After buying them she had $10. How much did each pencil cost?
Evaluate a + b when a = –16.2 and b = –11.4 A. –27.6 B. –4.8 C. 4.8 D. 27.6
What is the value of x? (-4) - x = 5
Find the quotient of 3,078 ÷ 27. A) 104 B) 109 C) 114 D) 119
Can someone help me with 5??? ASAP?
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org